Is rheumatoid arthritis in Indians associated with HLA antigens sharing a DR beta 1 epitope?. Issue 5 (May 1991) - Ollier, W E; Stephens, C; Awad, J; Carthy, D; Gupta, A; Perry, D; Jawad, A; Festenstein, H
Abstract : HLA class II antigens were identified in a group of 44 patients with rheumatoid arthritis (RA) originating largely from the north or northeast of the Indian subcontinent and resident now in east London. Compared with 67 locally typed east London Asian controls, the prevalence of three HLA-DR antigens was raised in the patients: DR1 18.2% v 6.0% chi 2 = 3.99, DR4 20.5% v 11.9% chi 2 = 1.48, and DRw10 27.3% v 8.9% chi 2 = 6.56. These differences were also found when the patients with RA were compared with a larger control group of 110 northern Indians: DR1 18.2% v 7.2% chi 2 = 4.02, DR4 20.5% v 7.2% chi 2 = 5.56, and DRw10 27.3% v 8.1% chi 2 = 9.7. Twenty five (57%) of the patients expressed at least one of these antigens. All patients were also characterised for HLA-Dw types by mixed lymphocyte culture typing. The prevalence of the HLA-DR4 associated Dw types in the patients was: Dw4 2.3%, Dw10 0%, Dw14 11.4%, and Dw15 6.8%. The DR beta 1 chains of DR1 and DRw10 together with the Dw types of DR4 other than Dw10 share amino acid residues in a region of the third hypervariable region considered to be critical in antigen presentation. It is concluded that RA in Indians is associated with these HLA antigens, and data from this study support the hypothesis of a cross reactive epitope common to HLA specificities associated with RA.